CHARACTER BUILDING CARING FOR THE ENVIRONMENT BASED ON LOCAL KNOWLEDGE IN URUG SOCIETIES BOGOR WEST JAVA - Fahmi Irfani; Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Rimun Wibowo (Tunas Geografi, 2020)
The objective of this research is to find out about character education cares environment based on local knowledge. The studies method used is ethnographic with qualitative approach. This method is implemented because the research is related to the social, traditional ceremony, customary societies, and social as well as cultural phenomena. The data are gathered through in-depth interview, observation, and documentation. The selection of respondent as samples uses purposive sampling technique. The result is probed meticulously through technique triangulation. The result shows that Urug societies have created societies character for the environment both social and ecology environment through applicating and conserve the tradition of heritage namely picking must ask for permission. The tradition is conducted collectively as societies habit when they release cultivating of paddies. There are two sorts of ceremony cultural such as Harvesting traditional ceremony (seren taun) and alms to earth (sedekah bumi). Permiting tradition in picking paddies must be conducted  because they have the view that a person must admit to the god before planting paddies through alms to earth. When the time for harvesting coming, societies propose admitting again before collecting paddies in the field. Once after paddies have been stored, Urug societies held harvesting ceremony collectively as a form that they have been gratefully when they obtain paddies yield. The other is Urug societies avoid greedy principle, it enacts Urug societies avoid from the environment devastated typically land because they farm paddies only one time in a year rather than 3-4 periods in a year. Other is Urug societies have applicated environment ethics both ecocentrism and biocentrism perspective to preserve nature from ravage. They also select agriculture as their venue to survive because they think that farmer is honest person and vanish envy temper in their life. Farmer embedded cooperation, mutual assisting, and mutual supporting among them.